WAV File Playback System by Two Different Methods Using a PSoC5LP - Julián R. Camargo L., César A. Perdomo Ch., Andrés L. Jutinico A. (International Journal of Advanced Science and Technology, 2020)
This paper presents the design of a WAV file playback system, widely used in the music world, using two different solution methods, each implemented in a PSoC5LP, thus showing the versatility and working power of the PSoC5LP manufactured by the North American company Cypress Semiconductor.